Tecbnology Evolution Strategy of Video Service Based on Open Internet - Qing Xiao; Siwei Wang (Dianxin kexue)
Video service is an important service for telecom operators.The advantages and disadvantages among IPTV,OTT TV and IPTV+OTT convergent architecture were compared,then the evolution direction of video service technology architecture of telecom operators was presented.Internet-1ike IPTV is either open and intelligent like OTT TV,or easy to operate and differentiated on service like IPTV.The evolution strategies of some key technologies,such as video codec,stream transportation,CDN,multicast,user interface,and end-to-end quality assurance,were proposed.